Psychological empowerment and job performance of star-rated hotels: The mediating role of emotional intelligence - Jennifer Cudjoe; Daniel Agyapong; Osman Light; Stephanie Efua Frimpong; Richard Kofi Opoku (Cogent Business & Management, 2023)
This paper examined the mediating role of emotional intelligence in the relationship between psychological empowerment and job performance. The quantitative approach was employed using a survey research design with a sample of 289 respondents from the star-rated hotels in the Central Region, Ghana. The explanatory research design was adopted to explain the relationships among psychological empowerment, emotional intelligence and job performance through the testing of hypotheses. PLS-SEM was used to test these hypotheses. It was found that psychological empowerment had a positive significant relationship with job performance in star-rated hotels. Furthermore, psychological empowerment had a positive relationship with emotional intelligence. Also, emotional intelligence had a positive significant relationship with job performance. Additionally, it was identified that emotional intelligence partially mediates the relationship between psychological empowerment and job performance. From the results, management of star-rated hotels should pay critical attention to employees' psychological empowerment as a job resource since it improves emotional intelligence and enhance job performance.
Keywords: 650; emotional intelligence; job performance; psychological empowerment; star-rated hotels